2012
DOI: 10.1111/j.1740-8261.2011.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

USEFULNESS OF A HALF‐FOURIER ACQUISITION SINGLE‐SHOT TURBO SPIN‐ECHO PULSE SEQUENCE IN IDENTIFYING ARACHNOID DIVERTICULA IN DOGS

Abstract: Single-shot turbo spin-echo sequences are heavily T2-weighted sequences that are exceptionally well suited to evaluate the subarachnoid space. In the T2-weighted fast spin-echo sequences that are used routinely in spinal magnetic resonance (MR) imaging, the subarachnoid space is not well differentiated from the surrounding epidural fat, which could lead to decreased detection of lesions of the subarachnoid space such as arachnoid diverticula. Our purpose was to determine the added value of a single-shot turbo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Retrospectively, readers for the current study reported that the T2WI hyperintense lesions seen in cases 1–3 seemed to be the “golf tee sign,” although this information was not available to surgeons before surgery. A “golf tee sign” can be theoretically differentiated from other conditions by using a combination of T2WI, T2*WI, fluid‐attenuated inversion recovery (FLAIR), and pre‐ and post‐contrast T1WI, as well as the single‐shot turbo spin echo sequence or half‐Fourier acquisition single‐shot turbo spin‐echo pulse sequence . However, differentiation of these lesions using low‐field MRI is not easy in the canine vertebral canal due to the smaller size vs. humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospectively, readers for the current study reported that the T2WI hyperintense lesions seen in cases 1–3 seemed to be the “golf tee sign,” although this information was not available to surgeons before surgery. A “golf tee sign” can be theoretically differentiated from other conditions by using a combination of T2WI, T2*WI, fluid‐attenuated inversion recovery (FLAIR), and pre‐ and post‐contrast T1WI, as well as the single‐shot turbo spin echo sequence or half‐Fourier acquisition single‐shot turbo spin‐echo pulse sequence . However, differentiation of these lesions using low‐field MRI is not easy in the canine vertebral canal due to the smaller size vs. humans.…”
Section: Discussionmentioning
confidence: 99%
“…A "golf tee sign" can be theoretically differentiated from other conditions by using a combination of T2WI, T2 * WI, fluid-attenuated inversion recovery (FLAIR), and pre-and post-contrast T1WI, [16][17][18] as well as the single-shot turbo spin echo sequence or half-Fourier acquisition single-shot turbo spin-echo pulse sequence. 20,21 However, differentiation of these lesions using low-field MRI is not easy in the canine vertebral canal due to the smaller size vs. humans. The image spatial resolution and contrast in T2 * WI varies with the field strength because of variations in signal-tonoise ratios.…”
Section: Discussionmentioning
confidence: 99%
“…MRI was therefore unable to identify the cause of the obstructive hydrocephalus. Recently, half‐fourier acquisition single‐shot turbo spin‐echo pulse (HASTE) sequences, which are heavily T2‐weighted sequences, have been proven to increase the sensitivity of MRI for diagnosis of spinal arachnoid diverticula . These MRI sequences were not available at the time of investigations of our cases and studies evaluating the usefulness of HASTE sequences for diagnosis of intracranial arachnoid diverticula are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The names refer to a single condition characterized by an accumulation of CSF and dilation of a focal area of the meninges, with most being congenital (primary), although some may be acquired (secondary). We use the most recent but anatomically correct term of Intradural arachnoid diverticulum …”
Section: Meningeal Cystsmentioning
confidence: 99%
“…An advantage over other imaging modalities is the ability to detect the presence of adhesions and septations, although this is not used as a diagnostic procedure . MRI is now the procedure of choice for the diagnosis of a spinal intradural arachnoid diverticulum (Figs and ), with a recent study suggesting the addition of a single‐shot turbo spin‐echo sequence gives a more than twofold increase in spinal intradural arachnoid diverticulum detection compared to a T2‐weighted sequence alone . However, the addition of a single‐shot turbo spin‐echo sequence only decreased the false negatives from 75% to 47.2%, meaning that some diverticulae went undetected.…”
Section: Meningeal Cystsmentioning
confidence: 99%